A high-performance Ce and Sn co-doped cathode material with enhanced cycle performance and suppressed voltage decay for lithium ion batteries. Issue 16 (November 2019) - Liu, Yanying; Li, Ranran; Li, Jianling; Yang, Zhe; Zhong, Jianjian; Wang, Zhen; Kang, Feiyu
Abstract: The advantages and disadvantages of the lithium-rich cathode material are outstanding. The advantages are large specific capacity, and the disadvantages are low conductivity and fast capacity attenuation. After more than a decade of research, it should be said that these two problems have been better resolved. But a trickier problem is that, as the cycle progresses, the discharge potential of the material gradually decreases. In many papers, this question has been deliberately or unintentionally avoided. The problem of potential attenuation is ultimately the problem of material structure stability. Herein, we develop a Ce and Sn co-doped cathode material with a stable structure by simple co-lithiation method. The electrochemical test results show that the Li1.2 [Mn0.525 Ce0.012 Sn0.003 Ni0.13 Co0.13 ]O2 (LMCSO-2) has good cycle stability, and after 100 cycles, the capacity retention rate is 90.21%, while the original material is only 71.25%. Moreover, the voltage decay is reduced from 0.5246 to 0.3078 V. This result is attributed to the synergistic effect of Ce and Sn is beneficial to the stabilization of the lattice structure, thereby reducing the Li activation energy and reducing the polarization during the redox reaction. In addition, a small amount of Ce and Sn can diffuse into the bulk phase during the co-lithiation process, thereby increasing the interplanar spacing and promoting Li + migration, significantly increasing the Li + diffusion rate.